Surface modification of a Mo-substrate to form an oxidation-resistant MoSi2 layer using a Si-saturated tin bath - Gamutan, Jonah; Miki, Takahiro (Nippon Tekko Kyokai, 2022)
Molybdenum disilicide (MoSi2) is one of the most heat and oxidation resistant materials used in high-temperature applications. In this work, the feasibility of forming an oxidation-resistant MoSi2 coating using a low-temperature Sn-Si bath by the hot dipping method was evaluated. It was found that a smooth and dense MoSi2 layer can be successfully synthesized on the surface of a Mo-substrate at 700 °C to 1000 °C. Using this method, MoSi2 can be synthesized more rapidly than using conventional methods and at much low operating temperatures. The diffusion through the product layer controlled the growth of the formed MoSi2 layer, and the growth rate was fastest at 800 °C. This was due to the replacement by the larger tin atoms that led to the expansion of the lattice, allowing the faster diffusion of silicon through the silicide layer towards the unreacted Mo-substrate. Oxidation resistance test at 1150 °C for 2 h confirmed that the MoSi2 layer formed by the present method protects the Mo-substrate from rapid oxidation at elevated temperatures.